KONFLIK PEREBUTAN TANAH SUCI TIGA AGAMA SAMAWI DI YERUSALEM (1980-2017 M) - Rahmawati, Hanifah; Muhammad Fahmi, Rezza Fauzi (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2022)
This study describes the conflict over the conflict over the holy land of three divine religions in Jerusalem during the Israeli period, namely, Judaism, Christianity and Islam, as the religion with the largest adherents on earth. The choice of this theme is considered important because of the dynamics of the struggle for territory that has civilizations that are connected to each other between the three divine religions, with the Prophet Ibrahim AS as the father of the prophets as well as the ancestor of their religion. The researchers took two theories that were used, among others, social action theory from Max Weber, and social conflict theory from Dahdrendorf. Yerusalem It has an important history for these three heavenly religions, presenting a sense of wanting to control and claim the holy city of Jerusalem as a city that belongs only to one religion. A re-reading of the history of Jerusalem has shown the historical spectrum of the social life of the three divine religions in Jerusalem.